2005
DOI: 10.1353/hsj.2005.0010
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Significance of Context: A Framework to Examine Equity and Reform in Secondary Mathematics

Abstract: The purpose of this article is to outline a framework that can be used to examine issues of equity and mathematics reform. Adapted from an opportunity-to-learn framework proposed by Tate (2004), this model includes factors related to time, quality, and design. This framework is applied to the cases of two secondary mathematics teachers to illustrate how these factors can operate to shape teachers' implementation of reform. The differences between the two cases point to the significance of teaching context with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Not only do students of color disproportionately attend inner-city schools plagued with a lack of resources (Kozol, 2005), but within diverse schools, students of color and students with low socioeconomic status are frequently assigned to Special Education classes, placed in low-track classes, or otherwise deemed incapable of performing highly (Lucas, 1999;McDermott, Goldman, & Varenne, 2006;Oakes, Joseph, & Muir, 2003). Teacher beliefs about their students play a prominent role in what they do in their classrooms (Rousseau & Tate, 2003), as do contextual factors such as time, curriculum available, and teacher professional development (Rousseau & Powell, 2005), and there is ample evidence that what teachers do matters quite a bit for student achievement, persistence, and processes of positioning and identification (Perry, 2003). In mathematics education, all of these aspects of schooling, and the relationships between them, need to be taken into account if we are to make real progress towards equity.…”
Section: Ideas and Identities 48mentioning
confidence: 99%
“…Not only do students of color disproportionately attend inner-city schools plagued with a lack of resources (Kozol, 2005), but within diverse schools, students of color and students with low socioeconomic status are frequently assigned to Special Education classes, placed in low-track classes, or otherwise deemed incapable of performing highly (Lucas, 1999;McDermott, Goldman, & Varenne, 2006;Oakes, Joseph, & Muir, 2003). Teacher beliefs about their students play a prominent role in what they do in their classrooms (Rousseau & Tate, 2003), as do contextual factors such as time, curriculum available, and teacher professional development (Rousseau & Powell, 2005), and there is ample evidence that what teachers do matters quite a bit for student achievement, persistence, and processes of positioning and identification (Perry, 2003). In mathematics education, all of these aspects of schooling, and the relationships between them, need to be taken into account if we are to make real progress towards equity.…”
Section: Ideas and Identities 48mentioning
confidence: 99%
“…From an OTL perspective, this narrowing of the curriculum in response to assessment is particularly problematic, as it is more likely to occur in high-minority classrooms (Darling-Hammond 1994 ;Lipman 2004 ;Madaus 1994 ;McNeil and Valenzuela 2000 ;Rousseau and Powell 2005 ;Shepard 1991 ;Weiss 1994 ) . For example, in a study of two predominantly African American schools, Lipman ( 2004 ) found that teachers were under substantial pressure to improve performance on the mandated standardized test.…”
Section: Assessment Policiesmentioning
confidence: 99%
“…In such situations, teachers often abandoned classroom practices, such as discourse practices that involve challenging intellectual engagement and that call on the students as resources, to meet the demands of high-stakes tests (Rousseau and Powell 2005 ) . In such situations, teachers often abandoned classroom practices, such as discourse practices that involve challenging intellectual engagement and that call on the students as resources, to meet the demands of high-stakes tests (Rousseau and Powell 2005 ) .…”
Section: Assessment Policiesmentioning
confidence: 99%
“…Rousseau and Powell consider equity in terms of reform implementations in their action study (2005). They found that time on task and quality of instruction were contextual factors found to influence reform implementation (Rousseau & Powell, 2005). These teacher factors were not addressed in this study.…”
Section: Literature Searchmentioning
confidence: 75%
“…Teacher factors effect reform teaching implementation (Nathan & Knuth, 2003;Woolley, Strutchens, Gilbert & Martin, 2010;Rousseau & Powell, 2005).…”
Section: Literature Searchmentioning
confidence: 99%